Manusia dalam Filsafat Eksistensi Karl Theodor Jaspers - Juhansar, Juhansar (FIKRAH, 2022)
Humans, as rational animals, are unique creatures with obligations and responsibilities. As rational animals, humans can process and solve their problems and strengthen the nature and purpose of their lives. This study aims to describe Karl Theodor Jaspers' views about humans from the perspective of philosophy, i.e., the enlightenment of existence and boundary situations. This article is descriptive qualitative philosophical research relays on a literature study. Literature data, primary and secondary, were analyzed using the philosophical hermeneutic method concerning verstehen and interpretation. This study shows that existentialism does not preoccupy the "eternal nature" of human beings because that nature is considered something that does not yet exist. Human "essence" is determined in human "existence." The "essence" is "becoming," which is unique to humans. Human existence can be seen in several theses, including unique and not objectified, "I" as a possible existence depends on its relationship with other existences, and existence has freedom. Second, humans as dasein are always contained in certain situations; as existence, humans are always encountered within the limits of the situation, i.e., fate, death, suffering, and struggle